Assessment of the energy properties of alkaline batteries - Dudojć, Bolesław; Mindykowski, Janusz (International Journal of Electronics and Telecommunications, 2026)
The paper presents the results of research based on an original method for assessing the energetic properties of alkaline batteries commonly available on the market. The study was carried out on a sample of AA size and AAA size batteries from several randomly selected manufacturers, under conditions of continuous discharge with a constant resistive load. A comparative analysis was performed on the basis of the total energy obtainable from a battery for a given load, as well as the energy efficiency factors of the useful energy and the potentially useful energy.